The Role of Notaries in Executing Location Permits for Housing Business Actors Using a Risk-Based OSS System - Agustina, Ayu (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
Electronically Integrated Business Licensing Services or Online Single Submission - Risk Based Management (OSS - RBA) which is a one-door investment licensing portal and is said to provide business convenience for all parties, including Small and Medium Enterprises (MSMEs), as stipulated in Government Regulation Number 5 of 2021 Concerning Risk-Based Business Licensing, which system was developed by the Investment Coordinating Board (BKPM). This study aims to elaborate on the roles and responsibilities of Notaries regarding the implementation of location permits for business actors with legal status in Indonesia, especially for Housing and Industrial businesses and to identify inhibiting factors and supporting factors for Notaries in carrying out their roles. The approach method in this study is a sociological juridical legal research method that studies the influence of society on empirical law and juridical where researchers carry out field studies by conducting interviews with informants. The specification of this research uses descriptive analysis. The type of data used in this study is primary data which includes the 1945 Law, Act No. 30 of 2004 in conjunction with Act No. 2 of 2014 concerning the Office of a Notary, Act No. 40 of 2007 concerning Limited Liability Companies, and Government Regulations Number 5 of 2021 concerning Risk-Based Business Licensing. The results of this study indicate that notaries are greatly assisted by the OSS RBA system, but there are still several obstacles both systemically, technically, in the field, and from human resources.Keywords: Location; Online; Permit; Submission.